RELATIONSHIP OF INVESTIGATION AUTHORITY IN DRUG CRIMES AFTER THE RULING OF LAW NUMBER 1 OF 2023 CONCERNING THE CRIMINAL CODE - Berton Lumban Tobing; Henry Aspan; Mhd. Azhali Siregar (International Journal of Synergy in Law, Criminal, and Justice, 2024)
Handling drug crimes in Indonesia faces significant challenges related to the differences in authority between the National Narcotics Agency (BNN) and the Indonesian National Police (Polri). Differences in arrest times and dualism in investigative authority have legal consequences that affect the human rights of suspects and the effectiveness of law enforcement. The enactment of Law Number 1 of 2023 concerning the Criminal Code (KUHP) brings major changes in the regulation of special crimes, including narcotics, which raises issues related to the principle of lex specialis. This study aims to identify and analyze changes in investigative authority, the legal implications that arise, and how to improve coordination between law enforcement agencies. Normative legal research methods are used to analyze relevant laws and court decisions. The results of the study indicate that the elimination of Article 111 of Law Number 35 of 2009 and its replacement with new provisions in Law Number 1 of 2023 requires adaptation from law enforcers. In addition, the implementation of rehabilitation as an alternative to punishment marks a shift towards a more restorative justice system.